2010
DOI: 10.1007/s00586-010-1321-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic thoracic scoliosis with rib head dislocation and intrusion into the spinal canal: a case report and review of literature

Abstract: The objective of the study was to report a rare occurrence of dislocation and intrusion of two rib heads into the spinal canal at the convex apex of a post-traumatic thoracic scoliosis in an adult in the absence of any neurological impairment. A 47-year-old male presented with a slowly progressive, post-traumatic thoracic scoliosis and a mild aching sensation over the posterior chest wall. The lower limb neurology and bowel and bladder function were normal. There was no clinical evidence of neurofibromatosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…There are numerous reports on costovertebral joint dislocation in cases of neurofibromatosis and scoliosis patients. [2][3][4][5] Kishen et al 6 reported post traumatic thoracic scoliosis with rib head dislocation in a case report however in this case the dislocation and trauma were chronologically separated by 32 years.…”
Section: Discussionmentioning
confidence: 80%
“…There are numerous reports on costovertebral joint dislocation in cases of neurofibromatosis and scoliosis patients. [2][3][4][5] Kishen et al 6 reported post traumatic thoracic scoliosis with rib head dislocation in a case report however in this case the dislocation and trauma were chronologically separated by 32 years.…”
Section: Discussionmentioning
confidence: 80%
“…Zand et al reported that no living bacteria were detected in the biofilm-formed dentin block after aPDT/PACT treatment with TB [38]. Kishen et al showed a bactericidal effect of a 5 log reduction by aPDT/PACT using MB and RB [39], and Akbari et al showed a 2.81 log reduction with nanographene oxide including ICG [27]. However, a number of studies have reported that the bactericidal effect of aPDT/PACT on E. faecalis biofilm was less than 90%.…”
Section: Discussionmentioning
confidence: 99%
“…Progression of a scoliotic curve increases the distance between the demifacets on the adjacent vertebrae in the convex apex of the curve and can potentially disrupt rib–vertebral articulation. Apical vertebral rotation may also play a role in disrupting rib–vertebral articulation [ 3 ]. As the scoliosis was of a higher degree in all the human cases [ 3 , 4 , 6 ] and since the biomechanics of the feline spine differ from those of the human spine, it is highly debatable whether this mechanism occurred in the reported case.…”
Section: Discussionmentioning
confidence: 99%
“…Apical vertebral rotation may also play a role in disrupting rib–vertebral articulation [ 3 ]. As the scoliosis was of a higher degree in all the human cases [ 3 , 4 , 6 ] and since the biomechanics of the feline spine differ from those of the human spine, it is highly debatable whether this mechanism occurred in the reported case. Scoliosis could have occurred before the accident and could therefore be an incidental finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation